Variasi Bahasa Sosiolek Dalam Series Album “Kalih Welasku” Di Channel Youtube Denny Caknan - Tyas Nur Wigati; Anggita Ketlin Bella Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2024)
Sociolectic language variations are one part of sociolinguistics. This research is entitled Sociolectic Language Variations in the Album Series